Cetuximab Inhibits Gastric Cancer Growth in vivo, Independent of KRAS Status - Shi, Min; Shi, Hailong; Ji, Jun; Cai, Qu; Chen, Xuehua; Yu, Yingyan; Liu, Bingya; Zhu, Zhenggang; Zhang, Jun (Current Cancer Drug Targets, 2014)
Mutation status of Kirsten rat sarcoma viral oncogene homolog (KRAS) may serve as a negative predictive marker of Cetuximab in treating colorectal cancer. The present study was to determine the role of KRAS status in EGFR antibody treatment for gastric cancer. KRAS status was clarified in SGC-7901 (wild type) and YCC-2 (G→A mutation) gastric cancer cell lines. Anti-proliferative and pro-apoptotic effects of Cetuximab were tested both in vitro and in vivo, the expression of phosphorylated (p) ERK, a downstream protein in EGFR-RAS-MEK pathway, was also analyzed. No significant in vitro anti-proliferative or pro-apoptotic effects of Cetuximab were observed in both cell lines. The growth of either SGC-7901 or YCC-2 gastric cancer xenograft was significantly inhibited by Cetuximab. Apoptosis was induced in SGC-7901 but not in YCC-2 xenografts after Cetuximab treatment. The expression of pERK was up-regulated in YCC-2 but not SGC-7901 xenografts after Cetuximab treatment. In conclusion, KRAS (G→A) mutation does not affect in vivo anti-cancer efficacy of Cetuximab.
Keywords: proliferation